Pengaruh Self Efficacy Dan Locus Of Control Terhadap Kinerja Karyawan PT. Tirta Investama - Hakiki, Iqbal; Sari, Maya (Jurnal Manajemen Akuntansi (JUMSI), 2022)
This study aims to explain the effect of self efficacy and locus of control on employee performance PT. Tirta Investama Medan. This research was conducted at the company PT. Tirta Investama. The number of samples used as many as 50 employees, with the method used is a survey method. The Data from this study are primary data obtained from observations, questionnaires and documentation. The analysis technique used is multiple linear regression. Based on the results of the analysis that has been done, it can be concluded that the positive and significant effect on the work of employees. Locus of control works positively and significantly on employee performance. Self-efficacy and locus of control work together on employee performance.